Analysis of the Daily Financial Recording System at PT Sari Alam Sukabumi - Awaliyah, Yulifah (Society : Jurnal Pengabdian Masyarakat, 2026)
The partner of this community service activity is PT Sari Alam Sukabumi which still implements a daily financial recording system manually using Microsoft Excel. The main problems faced by partners include the high risk of transaction recording errors, reliance on individual accuracy, potential errors in the calculation formula, and the daily cash recapitulation process which is less efficient and takes a relatively long time. This service activity aims to improve the quality and order of daily financial recording through assistance and evaluation of the recording system used by partners. The implementation method includes observation of the flow of recording cash in and cash out, assistance in the process of recording daily transactions, and analysis of the format and effectiveness of daily cash flow reports. The results of the activity show that the manual daily financial recording system is not optimal in supporting the accuracy, consistency, and speed of financial information presentation. Based on these findings, this activity recommends the implementation of a digital-based financial recording system or the use of more structured and integrated accounting software to improve work efficiency, minimize recording errors, and support more appropriate managerial decision-making. Overall, this mentoring activity makes a positive contribution in increasing partners' understanding of the importance of an accurate, systematic, and technology-based daily financial recording system.